Determinants that influence employee’s job performance at KYB-UMW Malaysia Sdn Bhd / Nur Farahin Sitiris and Nurfatin Nadhrah Abd Aziz - Sitiris, Nur Farahin; Abd Aziz, Nurfatin Nadhrah (2013)
Job performance is an individual expected output in term of quality and quantity. Job performance is important for organization success and productivity. There are four objectives of doing this study. The first objective is researchers need to identify employee level of job performance among the employee based on employee’s perception. This study tries also to determine the relationship between training program and job performance. Next, the aim of the research is to determine the relationship between workplace communications towards job performance. The last objective is to determine the relationship between workplace environment and job performance in KYB-UMW Malaysia Sdn. Bhd. This research is focusing in manufacturing company. The study was conducted among 80 respondents in KYB-UMW Sdn. Bhd. which is located in Telok Panglima Garang, Selangor. A descriptive research will be used as a researcher would like to understand the characteristics of the group in this study and distribution of questionnaire forms among employees in KYB-UMW Malaysia Sdn. Bhd. A correlation analysis will be used to identify the significant relationship among the variables and frequency, percentage and mean will be used for determining level of job performance. For findings, the three determinants show that there are positive relationship between training programme, workplace communication and workplace environment with job performance. From the findings, it indicates that training program is the most influence factor for job performance in KYB-UMW Malaysia Sdn. Bhd. The findings also indicate KYB-UMW Malaysia Sdn. Bhd possesses a high job performance level.